PENGARUH PELATIHAN, KEPEMIMPINAN DAN LINGKUNGAN KERJA FISIK TERHADAP SEMANGAT KERJA KARYAWAN DI PT. ASURANSI SINARMAS CABANG MEDAN - Pakpahan, Donok M; Samsir, Samsir; Arwinence, Arwinence (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to identify and analyze the effect of training, leadership and physical work environment on employee morale PT. Asuransi Sinar Mas Medan branch either partially or simultaneously. This research was conducted at PT Asuransi Sinarmas Medan branch located at Km No.1A Jl.Sisingamangaraja 6-7. North Sumatra, Indonesia. The population in this study were all employees of PT Asuransi Sinar Mas, Medan Branch in 2015 is numbered 43 people, while Sampling was done by census, where all members of the population sampled. Data used in this study are primary data and secondary data, quantitative and time series 2011-2015. The technique used by the author in collecting the data and information needed is the interview and questioner. Mechanical analysis using multiple regression analysis using SPSS 21.0. The results showed that in partial training and leadership and significant positive effect on morale, while the physical work environment variables and no significant negative effect on morale kerja.Hasil simultaneous research shows bahwapelatihan, leadership and physical work environment has a positive and significant impact on morale employee PT. Asuransi Sinar Mas branch in Medan.Keywords : Morale, Training, Leadership and Physical Work Environmen